Applications of Metal–Organic‐Framework‐Derived Carbon Materials. Issue 6 (13th December 2018) - Yang, Wenping; Li, Xiaxia; Li, Yan; Zhu, Rongmei; Pang, Huan
Abstract: Carbon materials derived from metal–organic frameworks (MOFs) have attracted much attention in the field of scientific research in recent years because of their advantages of excellent electron conductivity, high porosity, and diverse applications. Tremendous efforts are devoted to improving their chemical and physical properties, including optimizing the morphology and structure of the carbon materials, compositing them with other materials, and so on. Here, many kinds of carbon materials derived from metal–organic frameworks are introduced with a particular focus on their promising applications in batteries (lithium‐ion batteries, lithium–sulfur batteries, and sodium‐ion batteries), supercapacitors (metal oxide/carbon and metal sulfide/carbon), electrocatalytic reactions (oxygen reduction reaction, oxygen evolution reaction, and hydrogen evolution reaction), water treatment (MOF‐derived carbon and other techniques), and other possible fields. To close, some existing problem and corresponding possible solutions are proposed based on academic knowledge from the reported literature, along with a great deal of experimental experience. Abstract : Metal–organic‐framework‐derived carbons represent a promising kind of material for many fields of applications. Synthesis strategies, tailored material properties, and different electrochemical performances are prominent features of energy‐storage materials. Metal–organic‐framework‐derived carbons materials are comprehensively summarized, and evaluations are provided.